Vergangenes verhandeln : Spätantike Statusdiskurse senatorischer Eliten in Gallien und Italien - Meurer, Tabea L. (2019)
This study in cultural history addresses the value of past relations in Gallo-Roman and Italian discourses on social status in late antiquity. The volume examines how senatorial figures referred back to ancestors and ancient times to better position themselves in relation to their peers. At a broader level, it describes the negotiative processes surrounding the establishment of rank.